National Plan for School Improvement and Students First: the predictable nature of school education policy and the problem of student achievement. Issue 4 (4th July 2018) - Skourdoumbis, Andrew
ABSTRACT: This paper explores two Australian school education policy documents and the inputs they describe to boost student achievement. The paper suggests that current reform efforts in schooling like others previously configure student achievement in input–output terms confining school education policy to predictable inputs that sideline broader influences on educational output including, for instance, school funding. The national policy documents that are the subject of the case study in this paper are the National Plan for School Improvement and the current Students First. Student achievement is explored as an object of study that can be worked on by policy, including for across-the-board national 'non-educational' purposes. The analysis, critical in outlook, suggests that current school education policy trades on a predictable set of evidence-based inputs as correctives to declining levels of student achievement without weaving into the student learning equation the complex mix of relations that frame the educational system.